C-Reactive Protein in Various Degrees Severity of Psoriasis Vulgaris - Lita Setyowatie; Hari Sukanto; Dwi Murtiastutik (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Psoriasis vulgaris is an inflammatory, chronic, recurrent, and, non-contangious skin disease. The severity grade of psoriasis is measured with psoriasis area and severity index (PASI) score. C-reactive protein (CRP) is a sensitive, but not specific indicator of inflammation. In the active stage of psoriasis, highly increased CRP levels were found, whereas at remission they present a decrease level. Purpose: To evaluate the profile of CRP level in psoriasis vulgaris patients with various degress of psoriasis vulgaris severity in Dr. Soetomo Hospital Surabaya. Methods: Blood samples were collected in 16 patients to measure the CRP level in psoriasis vulgaris patients with various degrees of severity. Results: There were 16 patients (10 male and 6 female) with various degrees of psoriasis vulgaris severity (5 patients with mild severity, 8 patients with moderate severity, and 3 patients with severe severity). All CRP results were within normal limits. Conclusion: Many factors can influence the CRP levels, CRP can not be as single indicator of inflammation in psoriasis vulgaris. Key words: psoriasis vulgaris, c-reactive protein, PASI score.